Advancements in polyol synthesis: expanding chemical horizons and Néel temperature tuning of CoO nanoparticles - Baricic, Miran (2024)
The polyol synthesis of CoO nanoparticles (NPs) is typically conducted by dissolving and heating cobalt acetate tetrahydrate and water in diethylene glycol (DEG). This process yields aggregates of approximately 100 nm made of partially aligned primary crystals. However, the synthesis demands careful temperature control to allow the nucleation of CoO while simultaneously preventing reduction, caused by the activity of DEG. This restriction hinders the flexibility to freely adjust synthesis conditions, impeding the ability to obtain particles with varied morpho-structural properties, which, in turn, directly impact chemical and physical attributes. In this context, the growth of CoO NPs in polyol was studied focusing on the effect of the polyol chain length and the synthesis temperature at two different water/cations ratios. During this investigation, we found that longer polyol chains remove the previous limits of the method, allowing the tuning of aggregate size (20–150 nm), shape (spherical-octahedral), and crystalline length (8–35 nm). Regarding the characterization, our focus revolved around investigating the magnetic properties inherent in the synthesized products. From this point of view, two pivotal findings emerged. Firstly, we identified small quantities of a layered hydroxide ferromagnetic intermediate, which acted as interference in our measurements. This intermediate exhibited magnetic properties consistent with features observed in other publications on CoO produced in systems compatible with the intermediate formation. Optimal synthetic conditions that prevent the impurity from forming were found. This resolution clarifies several ambiguities existing in literature about CoO low-temperature magnetic behavior. Secondly, a regular relationship of the NPs´ TN with their crystallite size was found, allowing us to regulate TN over ~ 80 K. For the first time, a branching was found in this structure-dependent magnetic feature, with samples of spheroidal morphology consistently having lower magnetic temperatures, when compared to samples with faceted/octahedral shape, providing compelling evidence for a novel physical parameter influencing the TN of a material. These two findings contribute to the understanding of the fundamental properties of CoO and antiferromagnetic materials.